2020
DOI: 10.1080/13621718.2020.1823655
|View full text |Cite
|
Sign up to set email alerts
|

Effect of welding wires on fatigue property of 7N01-T4 aluminium alloy joints

Abstract: The effect of ER5356 and ER5087 welding wires on fatigue property of MIG-welded 7N01-T4 aluminium alloy joints was investigated. The microstructure of ER5087 welded joint is similar to that of ER5356 joint. However, the fusion zone of the welding joint with ER5087 has a smaller grain size than that of the joint with ER5356. The fatigue strength of joints welded with ER5356 and ER5087 is 105.9 and 103.2 MPa at 10 7 cycles. During the fatigue process, the crack initiation for joints welded using ER5087 is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The crack propagation follows a radial path and is generally observed in multi-pass welds. 31 The void size clearly confirms that the fatigue life was low, with cycles to failure less than 10 5 cycles. The crack propagation area was smaller and comparable with the specimens under a higher stress regime.…”
Section: Microstructural Examinationmentioning
confidence: 64%
See 1 more Smart Citation
“…The crack propagation follows a radial path and is generally observed in multi-pass welds. 31 The void size clearly confirms that the fatigue life was low, with cycles to failure less than 10 5 cycles. The crack propagation area was smaller and comparable with the specimens under a higher stress regime.…”
Section: Microstructural Examinationmentioning
confidence: 64%
“…These observations were in line with the previous works. 28,30,31 In addition, the existence of carbides acted as crack arrestors and enhanced the crack resistance. The residual stresses induced by thermal expansion during multi-pass welding and its subsequent contraction during solidification aided the fracture in the weld region.…”
Section: Resultsmentioning
confidence: 99%
“…A soft, ductile solid solution phase and a hard, brittle eutectic micro-constituent in the PMZ resulted in a loss of strength and ductility of the joint compared to the base metal (BM). Liu et al [15] reported that the crack initiation during fatigue loading of 7N01-T4 welded using ER5356 filler metal occurred from PMZ. Moreover, Sharahi et al [16] reported the harmful effect of PMZ on joint strength/ductility in AZ91 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to refining the structure by adding Zr element to the formation of Al 3 Zr. Liu et al [ 9 ] found the porosity and the eutectic melting in the heat affected zone led to crack initiation for ER5087 and ER5356 welded joints during the fatigue process, respectively. However, there are few reports comparing the effect of ER5356 and ER5087 welding wires on the corrosion properties of 7N01 aluminum alloy joint.…”
Section: Introductionmentioning
confidence: 99%